A Fast Model‐Predictive Speed Controller for Minimised Charge Consumption of Electric Vehicles. Issue 1 (26th November 2015) - Schwickart, Tim; Voos, Holger; Hadji‐Minaglou, Jean‐Régis; Darouach, Mohamed
Abstract: This paper presents the design of a real‐time implementable energy‐efficient model‐predictive cruise controller for electric vehicles including the driving speed reference generation. The controller is designed to meet the properties of a series‐production electric vehicle whose characteristics are identified and validated by measurements. The predictive eco‐cruise controller aims at finding the best compromise between speed‐reference tracking and energy consumption of the vehicle using an underlying dynamic model of the vehicle motion and charge consumption. The originally non‐linear motion model is transformed into a linear model mainly by using a coordinate transform. To obtain a piecewise linear approximation of the charge consumption map, the measured characteristics are approximated by a convex piecewise linear function represented as the maximum of a set of linear constraint functions. The reformulations finally lead to a model‐predictive control approach with quadratic cost function, linear prediction model and linear constraints that corresponds to a piecewise linear system behaviour and allows a fast real‐time implementation with guaranteed convergence. Simulation results of the closed‐loop operation finally illustrate the effectiveness of the approach.